Lithuania in the Texts by the Poets of the Victory at Orsha (1514) - Čiurinskas, Mintautas (Senoji Lietuvos literatūra, 2015)
After the loss of Smolensk in summer of 1514, in autumn of the same year an important victory was achieved against the troops of Muscovy at Orsha. Military strategic implications of the Battle of Orsha and territorial achievements were small in comparison with more important consequences on the international plane. It was a result of diplomacy and propaganda: the news about the victory against the Orthodox Muscovites have been effectively disseminated in Europe.  Occasional poetic works played important role in this process. Subsequently, most of them were included into the collection Carmina de memorabili cede Scismaticorum Moscouiorum published in Rome in 1515. In order to answer the question of how often Lithuania, Vilnius and Lithuanians are mentioned in such literary sources and also what kind of relevance these references present, occasional poetry written shortly after victory by such authors as Andreas Cricius (Pol. Andrzej Krzycki), Jacobus Piso (Hung. Jakab Piso) (including one letter written by him), Joannes Dantiscus (Pol. Jan Dantyszek), and others are analysed thoroughly in the article.
Keywords: -